The Mechanism of Applying the Cognitive Economy and Its Impact on Achieving Sustainable Development in the Arab Maghreb Countries: Application Requirements and Future Challenges (Al-Farooq Journal of Sciences, 2026)
The study examines the mechanism that how to applying and using the cognitive economy, and influences of its implications to achieving sustainable development in the Arab Maghreb countries. Furthermore, the study offers the scientific analysis  to explaining of the basic concepts for the cognitive economy and its components. On the other hand,  reviews the reality of cognitive performance, digital infrastructure and education in these countries and the extent of their connection to achieving the sustainable development aims. The study is counted on the descriptive analytical approach, using the analysis of some international indicators related to the Global Knowledge Index and the government reports of the countries, in addition to recent scientific articles and sources. According to the results, the cognitive economy is represented a key of strategic in the main for achieving the sustainable development aims in the Maghreb countries. For the reason of, it includes of the developing modern digital infrastructure, encouraging knowledge and innovation, and enhances the human capital. In spite of, the Maghreb countries are confronted the challenges and difficulties for applying the cognitive economy, for the reason that weak private and public funding, and the difficulty of transitioning from a traditional economy to a cognitive economy. Moreover, the digital skills are appeared the gaps in several Maghreb countries, that have a direct of impaction on the mechanism for applying the cognitive economy. To conclude, the study offers several recommendations that could support decision-makers and governments of the countries adopt a stimulating and advanced cognitive economy environment identify with achieving the sustainable development aims.
Keywords: Cognitive Economy, Sustainable Development, Innovation, Knowledge, Arab Maghreb.